2021
DOI: 10.1007/s11242-021-01542-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Distribution of Polytetrafluorethylene in Gas Diffusion Layers of Polymer Electrolyte Fuel Cells

Abstract: Polymer electrolyte fuel cells require gas diffusion layers that can efficiently distribute the feeding gases from the channel structure to the catalyst layer on both sides of the membrane. On the cathode side, these layers must also allow the transport of liquid product water in a counter flow direction from the catalyst layer to the air channels where it can be blown away by the air flow. In this study, two-phase transport in the fibrous structures of a gas diffusion layer was simulated using the lattice Bol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The calculated ranges of the effective conductivities and their comparison to the experimental results suggest an PTFE-fiber arrangement equivalent to an in-series arrangement is more likely. Studies have found that the PTFE also accumulates around the fiber-fiber intersections, 13,49,50 effectively improving the fiber-fiber thermal contact. However, we were limited in the XTM resolution and the fiber-PTFE contrast, which did not allow to resolve and separately segment the two solid phases.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated ranges of the effective conductivities and their comparison to the experimental results suggest an PTFE-fiber arrangement equivalent to an in-series arrangement is more likely. Studies have found that the PTFE also accumulates around the fiber-fiber intersections, 13,49,50 effectively improving the fiber-fiber thermal contact. However, we were limited in the XTM resolution and the fiber-PTFE contrast, which did not allow to resolve and separately segment the two solid phases.…”
Section: Resultsmentioning
confidence: 99%
“…Jeon [ 16 ] and Yang et al [ 17 ] adopted LBM to study the flow of liquid water due to different rib-channel widths and found that the two-phase behavior under the rib was the origin of the difference in fuel cell performance. Scholars have focused on the different wettability of fiber [ 18 ] and non-uniform distribution of PTFE [ 19 , 20 , 21 , 22 , 23 ], and the wettability of GDL has been demonstrated to have a significant effect on water transport. Hao and Cheng [ 18 ] compared highly hydrophobic GDLs with GDLs with nearly neutral wettability and considered wettability to be an important parameter controlling the two-phase behavior within the GDL.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolyte fuel cells (PEFCs) have gained increasing attention as power sources in automotive, portable, and stationary applications, due to rapid start-ups at low temperatures, quiet operation, high efficiencies, and possible zero emissions [1][2][3][4][5][6][7][8][9][10]. PEFCs are limited by the cost, performance, and durability of the device; as such, optimisation of the cell components is needed to facilitate wider commercialisation [8,[10][11][12]. The gas diffusion media (GDM) is a crucial component in the membrane electrode assembly (MEA) of the PEFC, as it facilitates the transport of reactant gases to the catalyst layer (CL) and has a substantial impact on the efficiency of the cell, as it regulates the heat and water produced because of the electrochemical reaction [6,9].…”
Section: Introductionmentioning
confidence: 99%